Feed Intake Response of Dumbo Catfish (Clarias gariepinus) to Pelleted Feed Containing 30% Protein - jesika idam kasih zebua; Martirah Wati Zendrato; Arismanto Zebua; Wawan Setiawan Hulu; Kalvin Berkat waruwu Berkat waruwu; Ratna Dewi Zebua; Destriman Laoli; Betzy Victor Telaumbanua (Jurnal Sains dan Teknologi Perikanan, 2026)
The highly profitable freshwater commodity in Indonesia is the dumbo catfish (Clarias gariepinus). In the cultivation process of catfish, feed plays a very significant role, contributing about 70% of all operational costs, with protein as the main component determining the appetite and growth of catfish. This study aims to describe the appetite response of dumbo catfish (Clarias gariepinus) to the provision of 30% protein pellet feed by observing feeding behavior and feed consumption patterns during the rearing period. The research was conducted in an observational manner at the community aquaculture pond in Hilina'a, Gunungsitoli. This study lasted for 2 months from April to May 2025. Fish were fed three times a day, and the feeding response was observed and analyzed descriptively. The results showed that the fish responded well to the feed provided, marked by a high level of enthusiasm during feeding and a stable eating pattern throughout the study period. The controlled environmental conditions also supported the fish's appetite to remain optimal. This research shows that 30% protein pellet feed can stimulate appetite and has the potential to improve the efficiency of catfish farming. Recommendations include the use of 30% protein feed along with good environmental management to achieve optimal and sustainable farming results.